Nutraceuticals: Beyond the Diet Before the Drugs - Santini, Antonello; Novellino, Ettore (Current Bioactive Compounds, 2014)
Diet and lifestyle are considered essential to promote and maintain the well-being as well as to prevent the onset of diseases linked to wrong lifestyle and dietary habits that can both determine pathological conditions. Many of these require pharmacological therapy; nevertheless, some can be prevented and taken care of with the use of nutraceuticals in the daily diet. Nutraceuticals are pharmacologically active substances that can be extracted from vegetal or animal food, concentrated and administered in a suitable pharmaceutical form. A nutraceutical hence is a food or part of a food that produces health beneficial effects, including the prevention and/or treatment of a disease. The proper use of these food-drugs can help to reduce and/or to slow the onset of diseases, and, in particular, all the lifestyle related health conditions, e.g. the metabolic syndrome, which is strongly depending on the improper lifestyle and incorrect dietary habit. The effectiveness of nutraceuticals can be seen with their inclusion in the daily diet as a preventive agent against the onset of disease and, therefore, beyond the diet but before the need to use a drug to treat the symptoms arising from the onset of a pathologic condition. Hypercholesterolemia, hypertension, obesity are some relevant and current examples of lifestyle related diseases for which a proper education and prevention that includes nutraceuticals in the diet is needed.
Keywords: health